Addicted to rehab : race, gender, and drugs in the era of mass incarceration - McKim, Allison (Critical issues in crime and society., 2017)
Sociologist Allison McKim gives an in-depth and innovative ethnographic account of two women's rehab programs, one located in the criminal justice system and one located in the private healthcare system--two very different ways of defining and treating addiction. Her study ultimately reveals a two-tiered system, bifurcated by race and class. Â Â